PENGARUH KUALITAS PELAYANAN JASA TERHADAP KEPUASAN NASABAH PT. WAHANA OTTOMITRA MULTIARTHA FINANCE PALEMBANG - Frecilia Nanda Melvani (JURNAL KOMPETITIF, 2020)
The research of this study is motivated by the increasingly intense competition in the business world.  This competition requires business people to be able to maximize the performance of their companies in order to compete in the market.  In companies engaged in services oriented to customer satisfaction, PT.  Wahana Ottomitra Multiartha Finance must always pay attention to communication by establishing excellent service activities that cause customer satisfaction.The purpose of this study is to determine how much physical evidence, reliability, responsiveness, assurance, and empathy affect customer satisfaction PT.  Wahana Ottomitra Multiartha Finance Palembang. The results of this study are partial physical evidence of a positive and significant effect on customer satisfaction PT.  Wahana Ottomitra Multiartha Finance Palembang of 3.2%, reliability partially has a positive and significant effect on customer satisfaction of PT.  Wahana Ottomitra Multiartha Finance Palembang of 26.4%, responsiveness partially positive and significant effect on customer satisfaction of PT.  Wahana Ottomitra Multiartha Finance Palembang by 10.6%, the partial guarantee has a positive and significant effect on customer satisfaction of PT.  Wahana Ottomitra Multiartha Finance Palembang by 15.1%, empathy is partially positive and significant effect on customer satisfaction of PT.  Wahana Ottomitra Multiartha Finance Palembang by 11.9%, as well as physical evidence, reliability, responsiveness, assurance, and empathy simultaneously have a significant effect on customer satisfaction PT.  Wahana Ottomitra Multiartha Finance Palembang of 67.2%. Keywords: Service Quality, Customer Satisfaction.